90TH ANNIVERSARY OF THE UNION OF PEDIATRICIANS OF RUSSIA - V. Yu. Al'bitsky; L. S. Namazova-Baranova (Union of pediatricians of Russia, 2017)
The article is dedicated to the 90th anniversary of the Union of Pediatricians of Russia. Studying the results of academic research, reports,  and resolutions  of congresses  and conferences  of Pediatrician  Societies,  it was observed  that discussions  organized  on pediatric forums which brought up actual problems occurring in pediatrics and clinical practice play an important role in decreasing the rate of child mortality and morbidity, saving millions of child lives in the USSR and modern Russia.